THE APPLICATION OF CURRICULUM 2013 IN LEARNING ENGLISH IN SMP KOTA PEMATANGSIANTAR - ORIJA SIMANJUNTAK; SAKINAH UBUDIYAH SIREGAR; CORNELIUS NATANAEL AMBARITA; YOSI AGNES RUMASI PAKPAHAN; NADIA JULYANTI NAINGGOLAN; SANDI ALDO SIPAHUTAR (CV KULTURA DIGITAL MEDIA, 2022)
This research was conducted to determine the process of applying scientific methods in teaching English and the difficulties faced by teachers in the teaching process in the classroom. The focus of this research is on the teaching process, especially the application of scientific methods. The research was carried out in three different secondary schools in Pematangsiantar. Participants in this study were nine junior high school English teachers from three junior high schools, grades 1, 2 and 3. The study used a descriptive approach and a qualitative design. Through file analysis, interviews and observations, data from this study were collected. Use thematic analysis to analyze data and introduce based on research questions. Then verify the data by deleting and checking members. The results showed that the application of the scientific method in the 2013 curriculum was in accordance with the rules and regulations. In the format of the Learning Implementation Plan (RPP), English teachers use various methods, strategies or learning techniques to clearly describe the steps of the scientific method (scientific method). However, in the process of learning English in the classroom, teachers rarely use this method. In the systematic scientific method, teachers usually do not follow the steps of implementing the method because they can better adapt to classroom conditions. Teachers do not apply this method optimally, because several factors will influence it. The difficulties associated with the adoption of the scientific method by teachers are: 1) lack of training or workshops involving multiple teachers in each school; 2) limited learning media in the school.